Helminthiasis Identification on Bengal Tiger (Panthera tigris tigris) - Dimas Raihan Syahputra; Tetty Barunawati Siagian (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2022)
Bengal tiger (Panthera Tigris) is a mammal in the big cat family. The decrease in the Bengal tiger population can be caused by helminth infections. The impact of helminth infection on Bengal tiger in short term does not show any clinical symptoms. The examination was carried out to identify gastrointestinal infections in Bengal tiger (Panthera Tigris) conducted at Maharani Zoo Lamongan, East Java. 5 samples of Bengal tiger feces were used for examination purpose. The examination of fecal samples on Bengal tigers was carried out qualitatively using the native method and the floating method. The results of the examination of 5 Bengal tigers at Maharani Zoo showed 1 positive for Ascarid eggs on native examination and on floating examination showed 2 positive samples for Strongylid eggs and 5 positive samples for Ascarid eggs. The percentage of helminthiasis in the Bengal tigers was 100% positive for helminth infection. The helminth infections at Maharani Zoo could be caused by damp cage, humid and dirty environment, food and water that were contaminated with helminth eggs. The treatment given for the Bengal tigers at Maharani Zoo used Â KalbazenÂ® that contains 1000mg albendazole.